Three essays on corporate finance - Yao, Jiaquan (2014)
This dissertation contains three essays on corporate finance. Essay One decomposes cash flow into a temporary and a permanent component, and show that the temporary component has little information content about future growth opportunities. We then study how firms allocate cash flow by estimating the cash flow sensitivities of various uses of cash flow with respect to the temporary component. We demonstrate several methodological advantages of our approach to alternative GMM methods. A key finding is that financially more constrained firms show significantly a lower sensitivity of investment, but a higher sensitivity of change in cash holdings, to the temporary component of cash flow than financially less constrained firms.